Impact of the COVID-19 pandemic on ophthalmologic outpatient care: experience from an Italian Tertiary Medical Center. (1st January 2021) - Savastano, Alfonso; Ripa, Matteo; Savastano, Maria Cristina; Kilian, Raphael; Marchini, Giorgio; Rizzo, Stanislao
Abstract: Purpose: To evaluate the impact the COVID-19-related national lockdown has had on Ophthalmologic Outpatient Care in an Italian Tertiary Medical Centre. Methods: We reviewed all the performances that were carried out as outpatient services at our department between 1 January 2020 and 30 November 2020. We compared data among four different periods: from 1 January 2020 to 17 March 2020 ("Pre-Lockdown"); from 18 March 2020 to 17 May 2020 (Lockdown); from 18 May 2020 to 2 November 2020 (Post-Lockdown) and from 3 November 2020 to 30 November 2020 (Regional Lockdown). Results: The overall number of performed routine outpatient visits per day (ROVs) was 11, 871 (Mean ± SD = 35.76 ± 17.81), whereas booked appointments (BAs) were 21272 (Mean ± SD = 63.86 ± 9.27), meaning a decline in the number of ROVs by 44.01%. (Mean ± SD = 28.10 ± 12.11, p <.001). Post-Lockdown and Regional Lockdown clinical activities, dropped respectively by 31 and 25.14% (38.87 ± 3.88 vs. 56.34 ± 11.06, p <.001 and 6.04 ± 4.51 vs. 56.34 ± 11.06 p <.001). The number of BAs per day decreased during the pandemic, going from a mean of 77.81 ± 2.57 booked appointments per day before the lockdown, to a mean of 53.14 ± 4.94, 61.80 ± 4.62 and 72.07 ± 1.09 appointments per day respectively during the lockdown, the post-lockdown and the regional lockdown periods. Conclusions: During the various lockdown periods, at our institution the volume of outpatient ophthalmological visits drastically dropped. This testifies the dramatic impact the COVID-19 pandemic has had on the supply of ophthalmic care.